THE INFLUENCE OF CORPORATE DEBT FINANCING ON EARNINGS QUALITY - CHRISTINE LEONARDI; IRWANTO HANDOJO (Jurnal Bisnis dan Akuntansi, 2018)
The objective of this research is to obtain empirical evidence about the influences of different levels of debt (whole debt, low debt, and high debt), operating cycle, firm size, sales volatility, cash flows volatility, losses, cost of debt, and Z-score to earnings quality. The population in this research is non-financial companies excluding service sector listed in Indonesia Stock Exchange during 2007-2013. Samples are obtained through purposive sampling method with observation period from 2011 to 2013, which only 83 of listed non-financial companies excluding service sector in Indonesia Stock Exchange meet the sampling criteria, resulting 245 data available are taken as the samples. The result shows that debt and losses have influence on earnings quality. Directionally, low debt has positive influence and high debt has negative influence on earnings quality. Firm size has influence on earnings quality when it is regressed with whole debt. Meanwhile, it has no influence when it is regressed with low and high debt. Sales volatility, cash flows volatility, cost of debt and Z-score have no influence on earnings quality.